A theoretical study on the simultaneous vapor-liquid and chemical equilibria in a highly restricted system - Molina, Matías José (2022)
In this work, the isomerization reaction of n-butane (C4(2)) to isobutane (iC4(1)) in the absence of other components is studied with the help of a model, in a relatively wide pressure range, both, under single fluid phase conditions and under vapor-liquid equilibrium conditions. In this last case the phase and chemical equilibrium are solved simultaneously. This binary system was chosen, among other considerations, because of the low number of degrees of freedom that it has, according to the phase rule for reactive systems. Such high level of restriction leads to a peculiar behavior that provides interesting insights, in particular on the simultaneous chemical and phase equilibrium. The C4(2) + iC4(1) system is represented in this work by the Soave-Redlich-Kwong equation of state coupled to quadratic mixing rules with binary interaction parameters set to zero. The required computation algorithms were developed in this work. The computed fluid phase equilibrium of this reactive system is a single univariant vapor-liquid equilibrium line. Such line ends at the only reactive vapor-liquid critical point that the system has. Some reactive isochores (or isotherms) were also computed. The obtained computation results show that for this system the conversion can be changed, under certain conditions, just by modifying the overall density, while keeping the temperature and the pressure at constant values.